2022
DOI: 10.5124/jkma.2022.65.9.558
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary treatment strategy for early colon cancer

Abstract: Background: Treatment for early colon cancer has progressed rapidly with endoscopic resection and minimally invasive surgery. Selection of patients without risk of lymph node metastasis is necessary before deciding on endoscopic resection for early colon cancer treatment. We aimed to review the optimal multidisciplinary treatment strategies for early colon cancer, including endoscopy and surgery.Current Concepts: Pathological risk factors include histologic grade of cancer cell differentiation, lymphovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…A multidisciplinary approach should be recommended to establish an optimized treatment strategy, minimize the risk of complications, and obtain excellent oncologic outcomes via patient-tailored treatment in patients with early colon cancer. This article is based on a study first reported in the J Korean Med Assoc 2022; volume (65): pages (558-567) [78], Multidisciplinary treatment strategy for early colon cancer: A Review…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach should be recommended to establish an optimized treatment strategy, minimize the risk of complications, and obtain excellent oncologic outcomes via patient-tailored treatment in patients with early colon cancer. This article is based on a study first reported in the J Korean Med Assoc 2022; volume (65): pages (558-567) [78], Multidisciplinary treatment strategy for early colon cancer: A Review…”
Section: Discussionmentioning
confidence: 99%